Development Strategy Certified Rice Seed Breeder Group Mitra Jaya Melati Ii Village Perbaungan District Serdang Bedagai Regency - Sasmita Siregar; Prayogi Pengestu (JASc (Journal of Agribusiness Sciences), 2020)
This study aims to determine the internal and external factors in the development of Mitra Jaya Cultivator Group certified rice seeds and to determine the development strategy of Mitra Jaya Cultivator Group certified rice seeds. This research was conducted in Mitra Jaya Nursery Group in Melati II Village, Perbaungan District, Serdang Bedagai Regency. Samples were taken by the Non Probability Sampling method with saturated sample techniques, while the data analysis method used was descriptive analysis and SWOT analysis. The results showed that internal and external factors of KP rice seed breeding. Mitra Jaya, namely strength (strengths), the quality of seeds is very good, using machines in producing it, setting its own selling price, strategic location. Weakness, capital is still weak, buying raw materials from other breeders, only producing a few varieties, not knowing the use of the digital market. Opportunities, demand continues to increase, the government recommends the use of certified seeds, has a clear target market, the use of digital technology in marketing. Threats (Treaths), increasingly fierce competition conditions, unstable rice prices, climate change or unfavorable weather, pest and rice plant diseases. Based on a SWOT analysis the strategy is carried out using the SO (Strenghts-Opportunities) strategy, which is Utilizing the quality of seeds produced in setting prices to meet the increasing demand for agents / farmers and utilizing the digital market in promoting products.